Systematische Bibliographie der Hethitologie 1915-1995, zusammengestellt unter Einschluss der einschlägigen Rezensionen (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1998)
The people of the Hittites (ca. 1700-1200 B.C.) have been the object of serious study for more than eighty years now. Consequently our knowledge of these Indo-European Anatolians has grown at an enourmous pace. One may therefore rigthly conclude that the flow of scholarly literature in monographs, journal articles, Festschriften et cetera has reached a point where hardly any scholar can claim an overview anymore. This systematic bibliography of Hittitology covers the scholarly production from 1915-1995. The authors have aimed at exhaustiveness for Hittitologists. As Hittitology can not be isolated from the studies of adjacent contemporary (Anatolian) peoples, also relevant important contributions on for example the Chatti, Churrites, Luwians and other cultures have been taken into account. The work is divided into nine chapters: 1. General (Reference Works, Festschrifte, Congresses, et cetera); 2. Archaeology, Anthropology, Collections; 3. Script, Epigraphy; 4. Language and Philology, Ethnic Groups; 5. Geography; 6. Social Relations; 7. History; 8. Religion; 9. Cultural History. With geographical index and an index of authors and reviewers. 'A reliable bibliography is one of the basic elements for every serious library.' The Systematische Bibliographie der Hethitologie 1915-1995 was compiled by Vladimír Sou_ek and Jana Siegelová, and originally published with cooperation of the Prague Narodni Museum. The work is distributed exclusively by Brill and has been incorporated in the series Handbook of Oriental Studies 1.